Thoracic Limb Morphology of the Ring‐tailed Lemur (Lemur catta) Evidenced by Gross Osteology and Radiography. (8th August 2014) - Makungu, M.; Groenewald, H. B.; du Plessis, W. M.; Barrows, M.; Koeppel, K. N.
Summary There is limited information available on the morphology of the thoracic limb of the ring‐tailed lemur (Lemur catta). This study describes the morphology of the thoracic limb of captive ring‐tailed lemurs evidenced by gross osteology and radiography as a guide for clinical use. Radiographic findings of 12 captive ring‐tailed lemurs are correlated with bone specimens of three adult animals. The clavicle is well developed. The scapula has a large area for the origin of the m. teres major. The coracoid and hamate processes are well developed. The lateral supracondylar crest and medial epicondyle are prominent. The metacarpal bones are widely spread, and the radial tuberosity is prominent. These features indicate the presence of strong flexor muscles and flexibility of thoracic limb joints, which are important in arboreal quadrupedal locomotion. Furthermore, an ovoid ossicle is always seen at the inter‐phalangeal joint of the first digit. Areas of increased soft tissue opacity are superimposed over the proximal half of the humerus and distal half of the antebrachium in male animals as a result of the scent gland. Knowledge of the morphology of the thoracic limb of individual species is important for accurate interpretation and diagnosis of musculoskeletal diseases.